MENDUKUNG PENGEMBANGAN USAHA MIKRO DAN KECIL, MENGEMBANGKAN POTENSI PERTANIAN DAN PENANGGULANGAN STUNTING DESA GUNUNG KARAMAT - Afiyah, Dinda; Rifqi Pamungkas; Akbar fadillah; Dio Damas Permadi; Muhammad Hidyat; Utmy Sukmayu Saputri (LPPM Universitas Nusa Putra, 2025)
Community Service Program (KKN) is a form of community service based on the Tridharma of higher education. The purpose of this Community Service Program (KKN) is to provide opportunities for students to devote themselves to society and contribute to solving problems and developing potential in the village. After conducting observations, there are several problems such as, land shifting disasters, Gunung Karamat Village also faces the problem of high stunting rates among children, MSMEs in Gunung Karamat Village, namely Coffee, the sale of coffee has not entered online stores and well-known cafes so that it hampers marketing and in terms of education or academics, in Gunung Karamat Village it can be considered lacking because the level of education from schools is only PAUD, SD, and SMP as well as the facilities in the realm of schools are not optimal. Therefore, we carry out several activities such as conducting socialization about disaster mitigation, socialization about stunting prevention and providing vitamins for children who are indicated to be stunted, and we help facilitate sales such as making branding videos and creating Shopee accounts to make marketing easier.